Lincoln's Campaign Biographies - Horrocks, Thomas A. (Book collections on Project MUSE., 2014)
During the 1860 and 1864 presidential campaigns, Abraham Lincoln was the subject of over twenty campaign biographies. In this innovative study, Thomas A. Horrocks examines the role that these publications played in shaping an image of Lincoln that would resonate with voters and explores the vision of Lincoln that the biographies crafted, the changes in this vision over the course of four years, and the impact of these works on the outcome of the elections. Horrocks investigates Lincoln's campaign biographies within the context of the critical relationship between print and politi.